POTENTIALITE TECHNOLOGIQUE DES LACTOCOQUES ISOLEES DU LAIT CRU DE CHEVRE - HAMAR, Hanane (My University, 2018)
Our research project is based on two components the first is the Lactococcus were isolated from raw milk of goat, identified and characterized by phenotypic properties, physiological and biochemical, as regards the second part is about the exploitation of potential technological study to reach theflavoring activity, Study of the kinetics of strains (C4, C10, C16), activityproteolytic, lipolytic, activity exopolysaccharide and study of the antibacterial activity of Lactococcus kind (method of double layer) The results showed that major espese Lactococcus isolated from goat milk are Lactococcus lactis subsp. lactis 37%, Lactococcus plantarum 19%, Lactococcus lactis subsp. lactisbiovar. Diacetylactis 19%, Lactococcus lactis subsp. Cremoris 12%, Lactococcus reffinolactis 13%. and alsoindicate that the sets of strains have a good power acidifying, proteolytic, lipolytic, exopolysaccharide, flavoring, and probiotics skills (tolerance to acidity and antimicrobial pouvour) have also proved interesting
Keywords: lait de chévre; bactéries lactiques; lactococcus; potentialite technologique; milk goat; lactic acid bacteria; technological potentiality